PLANT ETNOBOTANY FOR POSTPARTUM CARE BY MANDAILING TRIBE IN VILLAGES AROUND THE BATANG GADIS NATIONAL PARK AREA, MANDAILING NATAL REGENCY - Fitriana Nur Nasution; Aswarina Nasution; Ahmad Shafwan S Pulungan (Universitas Negeri Medan, 2023)
Marsidudu is a smoking process to accelerate the discharge of postpartum blood so that the body becomes healthy after childbirth. The ingredients used in the marsidudu come from plants. According to the Mandailing tribe, currently, the marsidudu has begun to be abandoned by the community due to the influence of modernization. This study aims to reveal and document belief systems, local knowledge, plant utilization practices, and plant cultural significance (Index of Cultural Significance) plants used by the Mandailing Tribe in villages around the Batang Gadis National Park area related to plants in the marsidudu. The research location is in 2 villages around the Batang Gadis National Park, Mandailing Natal Regency. Data was collected through semi-structured interviews, participatory observation, documentation, collection of plant samples, and making herbarium. The data were analyzed descriptively qualitatively and quantitatively. The results showed that the marsidudu believed to be able to keep mothers and babies away from subtle-being disorders and has benefits for the health of the mother and baby. There are 13 plant species covering 9 families used in the marsidudu. The most widely used species come from the Asteraceae family, which is as many as 3 species. The dominant herb habitat is used in the marsidudu which includes 6 plant species. The part/organ of the leaf that is most widely used in the marsidudu. The plants used in the marsidudu are placed on coconut husks until the plants start to smoke. When the plants start to emit smoke, the mother covers the body with a sarong and spreads her legs wide with the uterus perpendicular to the burned plant. Tangkal langkeso (Artemisia vulgaris L.) and tindo tasik (Clerodendrum serratum L.) have important cultural values (Index of Cultural Significance) in the high category of the marsidudu by the Mandailing Tribe.